2020
DOI: 10.1038/s41598-020-71292-4
|View full text |Cite
|
Sign up to set email alerts
|

Two potential equilibrium states in long-term soil respiration activity of dry grasslands are maintained by local topographic features

Abstract: Soil respiration of grasslands is spatio-temporally variable reflecting the changing biological activities of the soil. in our study we analysed how the long-term soil respiration activities of dry grasslands would perform in terms of resistance and resilience. We also investigated how terrain features are responsible for response stability. We conducted a 7-year-long spatial study in a Hungarian dry grassland, measuring soil respiration (R s), soil temperature (T s) and soil water content (SWC) along 15 measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…The responses of R s to soil moisture and T s were investigated in several studies, which already reported that the correlation between R s and T s as well as SWC and T s differed in temporal and spatial studies (Allaire et al, 2012;Almagro et al, 2009;Fóti et al, 2020;Herbst et al, 2009;Lellei-Kovács et al, 2016;Moyes and Bowling, 2016;Shi et al, 2011;Tang et al, 2020). Our study is consistent with these findings, because R s showed positive correlation with SWC and LAI.…”
Section: The Spatiotemporal Explanatory Factors Of R Ssupporting
confidence: 91%
See 4 more Smart Citations
“…The responses of R s to soil moisture and T s were investigated in several studies, which already reported that the correlation between R s and T s as well as SWC and T s differed in temporal and spatial studies (Allaire et al, 2012;Almagro et al, 2009;Fóti et al, 2020;Herbst et al, 2009;Lellei-Kovács et al, 2016;Moyes and Bowling, 2016;Shi et al, 2011;Tang et al, 2020). Our study is consistent with these findings, because R s showed positive correlation with SWC and LAI.…”
Section: The Spatiotemporal Explanatory Factors Of R Ssupporting
confidence: 91%
“…On the other hand, surface heterogeneity was lower under the grove due to the fact that the seeds of tree species in this habitat can only germinate in ideal depressions, where a sufficient amount of water can accumulate (Erdős et al, 2014). In the context of spatial heterogeneity, deeper positions contain more carbon due to accumulation, resulting in higher R s activity and SWC (Fóti et al, 2020).…”
Section: The Influence Of Cardinal Directions and Topographymentioning
confidence: 98%
See 3 more Smart Citations